Atividade antimicrobiana do mel de abelhas Apis mellifera L. e Melipona subnitida L. frente amostras bacterianas multirresistentes de Staphylococus aureus e Pseudomanas aeruginosa - Andrade Neto, Francisco Vicente de (2010)
In recent years, bacterial resistance to multiple drugs has increased due to the indiscriminate use of antibiotics, widely used to treat infections. This situation has challenged scientists to search for new alternatives such as natural substances, in order to develop new guidelines with antibacterial recognized. Natural products have been used for thousands of years by the popular medicine for several purposes. Among them is the honey, a product resulting from collection and exudates of various plants by bees. Besides its nutritional value, honey is receiving greater attention by the scientific evidence of its medicinal effects through its therapeutic properties, especially the antimicrobial activity. Thus, this study aims to evaluate the in vitro antimicrobial activity exerted by the honey bee Apis mellifera L. and Melipona subnitida L. on the microorganisms Metilcilina Resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa isolated from hospital samples. The honey samples used were obtained from hives maintained in the region of Serra do Mel, RN, Brazil, and the Technological Center of Beekeeping (CETEC) of UFERSA, Mossoró, RN, Brazil. Data on the physical and chemical properties were used for characterization of honey from Apis mellifera L., in addition to color, consisting of honey-colored (mC), light amber (mAC) and dark amber. The method of Kirby and Bauer, diffusion in Mueller Hinton agar was used to evaluate the antimicrobial activity of honey, using wells 06 mm in diameter, in the presence of 06 bacterial isolates. To control the experiment, were conducted in parallel with different antibiograms commercial antibiotics, using the strains ATCC 25953 and ATCC 27853. The test results showed a susceptibility to MRSA, reaching inhibition zones of up to 31 mm in diameter. However, for Pseudomonas aeruginosa, the zones of inhibition reached 19 mm, considered minor when compared to produce about MRSA, probably due to factors intrinsic resistance to Pseudomonas aeruginosa. Therefore, this study identified to date for a therapeutic potential of this natural product, in particular the antimicrobial activity of honey from Apis mellifera L., proving to be the more efficient than honey from Melipona subnitida